Assessment of Macronutrient Dynamics in a Tropical Watershed: A Study from Bengkulu River and Estuary Indonesia - Wiwit, Wiwit; Ikhsani, Idha Yulia; Nurhamidah, Nurhamidah; Oktiarni, Dwita; Wong, Kuo Hong (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
This study assesses the sources, transport, and distribution of macronutrients, including nitrate, nitrite, silicate, and phosphate, starting from the upper stream of the Bengkulu River, which is the biggest river in Bengkulu Province, to the coastal seawater of the eastern tropical Indian Ocean. The sampling was conducted using an acid-washed polypropylene beaker and placed in acid-cleaned 5 L polyethylene containers during the dry season in July 2024. The water samples were collected from the surface waters of 15 stations. The macronutrients in the water samples were determined using a spectrophotometer UV-Vis following the Strickland and Parsons method. Macronutrient analysis was conducted in LATERIO BRIN, Jakarta, Indonesia. The concentration of analysed macronutrients ranged from 0.005 - 0.058 mgN-NO3/L for nitrate, <0.001 - 0.014 mgN-NO2/L for nitrite, 0.163 - 9.314 mgSi-Si(OH)4/L for silicate, and 0.01 - 0.085 mgP-PO4-/L for phosphate. Several stations, including Stations 6, 10, and 14, exhibited relatively elevated nitrate concentrations, which were further supported by similarly high phosphate levels. Stations 6, 10, and 14, situated near areas of intense anthropogenic activity in Bengkulu City, suggest that human-induced inputs have enriched the water environment with macronutrients. The highest silicate concentration was observed at Station 1, located upstream in the Bengkulu River. This aligns with previous findings and underscores the role of weathering processes in controlling silicate distribution. Compared to the macronutrient concentration guidelines for river water set by Indonesian Government Regulation 2021 No. 22, the nitrite concentrations at certain river stations exceeded the safety threshold for aquatic biota. In contrast, nitrate and phosphate levels remained within the safe range.